A Study of Indian Thespian Folklore: - (Journal of Advances and Scholarly Researches in Allied Education, 2018)
Indian Theatre is a fusion craft form in India with a fusion of elements from music, dance, pantomime, versification, epic and ballad recitation, graphic and plastic arts, religion and festival peasantry. The Folk theatre having roots in endemic culture is embedded in provincial identity and social values. Likewise providing mass entertainment, it helps Indian society as primitive tools of interpersonal, inter-group and inter-village communication for ages. Indian theatre has been used broadly in India to multiply critical social, political and cultural issues in the form of theatrical messages to create awareness among the people. As aprimitive form it breaks all kinds of formal boundary of human conversation and appeals directly to the people. Realising the vital and powerfulness of the traditional medium, the First Five Year strategy projected that people in rural areas should be approached through traditional-folk forms of conversation in addition to electronic media. Different forms of Folk Theatre in India are traditional way of conversation and constitute a potential source for conveying messages for Social, Economic and Cultural Development which ultimately helps in overall National Development.